Magnetic domain study in a Fe3GaTe2 ferromagnet with strong perpendicular anisotropy using magnetic force microscopy - Lee, Jungsub (2024)
We investigate the magnetic domain behavior of bulk Fe3GaTe2, a van der Waals (vdW) ferromagnet characterized by a Curie temperature (Tc) of 350-380 K and significant perpendicular magnetic anisotropy (PMA). Using magnetic forcé microscopy, we present the evolution of magnetic domains during cooling from Tc to 300 K, and analyze magnetic domain images along the hysteresis loop at 4.2 K. Our observations reveal a strong temperature-dependent domain structure. From room temperature to Tc, we observe the coexistence of stripe, bubble, and surface spike domains. In contrast, in the zero field cool state at 4.2 K, irregular stripe and enclosed ring domains predominate. The correlation between global and local magnetization suggests that the hysteretic behavior in the magnetization results from the rapid nucleation of a few stripe domains evolving into intricate dendritic patterns, a phenomenon not previously observed in other vdW systems. These findings highlight the delicate balance among interlayer exchange coupling, termal fluctuations, and PMA in the formation of various domains in a 3D vdW system, where shape anisotropy is minimized.